2020
DOI: 10.1519/jsc.0000000000002475
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Autonomic Responses to In-Season Training Among Division-1 College Football Players

Abstract: Despite having to endure a rigorous in-season training schedule, research evaluating daily physiological recovery status markers among American football players is limited. The purpose of this study was to determine if recovery of cardiac-autonomic activity to resting values occurs between consecutive-day, in-season training sessions among college football players. Subjects (n = 29) were divided into groups based on position: receivers and defensive backs (SKILL, n = 10); running backs, linebackers and tight-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…3). This initial response to training is consistent with the between-position LnRMSSD responses observed during spring camp [18] and the early competitive period [33]. Possible explanations for the reduction in LnRMSSD among linemen have previously been discussed [18] and pertain to differences in aerobic fitness, body mass and composition, anaerobic workloads, and fluid losses between groups [12].…”
Section: Discussionsupporting
confidence: 84%
“…3). This initial response to training is consistent with the between-position LnRMSSD responses observed during spring camp [18] and the early competitive period [33]. Possible explanations for the reduction in LnRMSSD among linemen have previously been discussed [18] and pertain to differences in aerobic fitness, body mass and composition, anaerobic workloads, and fluid losses between groups [12].…”
Section: Discussionsupporting
confidence: 84%
“…Despite a strong inverse relationship between RHR and LnRMSSD, LnRMSSD demonstrated stronger associations with ASRM at both the group and individual level. Previous investigations have demonstrated that ultra-short LnRMSSD was more sensitive than RHR for reflecting responses [ 3 ] and fitness changes [ 39 ] to training among team-sport athletes. Despite a greater sensitivity to training and perceptual responses, interpreting LnRMSSD in conjunction with RHR is still encouraged for other reasons, such as detecting parasympathetic saturation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resting heart rate variability (HRV) is considered a global marker of homeostasis [ 1 ] and is widely implemented as an indicator of training adaptation in the applied sports setting [ 2 , 3 , 4 , 5 , 6 ]. For example, HRV has been shown to reflect changes in performance [ 4 ] and training load [ 7 ] among competitive swimmers.…”
Section: Introductionmentioning
confidence: 99%
“…Player monitoring strategies and data analysis techniques in collegiate football are generally managed by performance staff. Microsensor-derived training load, subjective well-being, and ultra-short heart rate variability (HRV) represent a few of the measures currently being used by American college football teams in an effort to optimize player health and performance [1,2,3,4]. However, effective use of player monitoring tools such as HRV requires interpretation of the data in appropriate context given its sensitivity to a variety of physiological, psychological, and environmental factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms are poor indicators of neurological recovery, and standard clinical tests have been found inadequate for detection of subtle abnormalities that can persist beyond return to sport participation [10,11]. A number of published reports have established HRV as a reliable marker of autonomic dysregulation after SRC [10,12,13], potentially confounding interpretation of fatigue-induced alterations among collision-sport athletes [1,2,14,15,16]. Daily HRV averaged over a period of time (e.g., 1–2 weeks) reflects mean parasympathetic activity while its coefficient of variation (CV) reflects the magnitude of daily HRV fluctuations.…”
Section: Introductionmentioning
confidence: 99%